The structure and degree of dependence in government bond markets - Dimic, Nebojsa; Piljak, Vanja; Swinkels, Laurens; Vulanovic, Milos (Elsevier, 2021)
Our study provides new evidence on asymmetric dependencies in international government bond markets, by examining bonds from developed, emerging, and frontier countries, using a quantile regression methodology. We find that the dependence structure for emerging and frontier markets significantly changes during financial crisis periods, which we show has important implications for international diversification of investment strategies. Moreover, we also examine in detail stock–bond correlations and uncover several instances of decoupling. In contrast, developed markets exhibit a more stable dependence pattern. In addition, we document that the degree and structure of dependence vary when foreign currencies are hedged or unhedged, and across bond maturity segments.
Keywords: Dependence structure; Emerging and frontier markets; Quantile regression; Sovereign bonds; financial crises; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|